Aerobic BTEX biodegradation increases yield of perfluoroalkyl carboxylic acids from biotransformation of a polyfluoroalkyl surfactant, 6:2 FtTAoS. Issue 3 (3rd February 2022) - Olivares, Christopher I.; Yi, Shan; Cook, Emily K.; Choi, Youn Jeong; Montagnolli, Renato; Byrne, Adam; Higgins, Christopher P.; Sedlak, David L.; Alvarez-Cohen, Lisa
Abstract : The presence of BTEX in AFFF-impacted soils increased the yield of terminal transformation products from polyfluorinated surfactant 6:2 FtTAoS. Aromatic oxygenases are likely responsible for direct oxidation of the thioether moiety. Abstract : Aqueous film-forming foams (AFFFs) are important sources of per- and polyfluoroalkyl substances (PFASs) in soil, groundwater, and surface water. Soil microorganisms can convert polyfluorinated substances into persistent perfluoroalkyl acids, but the understanding of co-contaminant stimulation or inhibition of PFASs biotransformation is limited. In this study, we investigate how aerobic biotransformation of polyfluorinated substances was affected by common AFFF co-contaminants, such as gasoline aromatics: benzene, toluene, ethylbenzene, and o -xylene (BTEX). We performed aerobic microcosm studies by inoculating AFFF-impacted soil with medium containing 6:2 fluorotelomer thioether amido sulfonate (FtTAoS) and either diethyl glycol monobutyl ether (DGBE), a common AFFF ingredient, or BTEX compounds as the main carbon and energy source. BTEX-amended microcosms produced 4.3–5.3 fold more perfluoroalkyl carboxylates (PFCAs) than DGBE-amended ones, even though both organic carbon sources induced similar 6:2 FtTAoS biotransformation rates. In enrichments of AFFF-impacted solids selecting for BTEX biodegradation, we detected the presence of genes encoding toluene dioxygenase as well as larger abundances of transformation products from thioether oxidation that complement larger quantities of terminal transformation products. Our findings indicate that enrichment of BTEX-degrading microorganisms in the AFFF-impacted soil enhanced the conversion of 6:2 FtTAoS to PFCAs. These results provide insights into the high ratio of PFAAs to precursors at AFFF-impacted sites with history of BTEX bioremediation.